Pembelajaran Biologi dalam Kurikulum Merdeka di Sekolah Urban - Anisa Intan Setyani; Dwi Kurnia Putri; Revita Alief Pramesti; Santi Suryani; Wahyu Fitria Ningrum (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The Merdeka Curriculum can be considered as an option that exists to solve the problem of learning loss factors from online learning due to the Covid-19 pandemic.  This study aims to determine educational problems in urban schools that have implemented the Merdeka Curriculum.  The method that the researchers used was the observation method, as well as interviews for teachers and questionnaires for students.  Based on research conducted, there are educational problems in learning using the Merdeka Curriculum in urban schools that are experienced by students, including lack of focus, low literacy skills, unable to collaborate with friends, and unable to manage time properly.  Suggestions that can be given for problems that occur include the teacher being able to hold ice breaking so that students can switch for a while from cellphones, use media and learning methods that are more interesting, students learn more deeply independently and learn to manage time.  Some students are still adjusting to the process and learning materials using the Independent Curriculum.  Therefore, the teacher's role is very important in helping students to guide and explain the material.